ANALISIS VARIABEL YANG MEMPENGARUHI PENDAPATAN NELAYAN DI SEUMELU - Yasrizal Yasrizal (Universitas Teuku Umar, 2018)
Simeulu is an island in the Indian Ocean having a large coastal area, 36 percent of the population are fishermen. 311,351 residents of Simeulu live below the poverty line. Capital, employment, catches and prices determine the income earned by fishermen. Therefore, it is necessary to examine the influence of capital, work experience, price and catch on the income of fishermen in Simuelu District. This study uses primary data taken using random sampling method. The number of samples in this study were 30 fishermen taken from the total population using incidental sampling method. The approach used in this study is quantitative. Data analysis tools are used using multiple linear regression methods. The results of multiple linear regression show that the variables of capital, work experience, prices and catches simultaneously affect the income of fishermen in Simeulu. The variables that have the most influence on fishermen's income are capital, starting from the use of the vehicle, the type of feed, the type of ship and the technology used. In conclusion, capital, selling price and fish catch affect fishermen's income.Keywords: Fisherman Revenue, Work Experience, Fish and Capital Prices